2008
DOI: 10.2139/ssrn.1183543
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Persistent Food Insecurity: A Paradox of Place and Circumstance

Abstract: Abstract:Survey data from a USDA-funded multi-state longitudinal project revealed a paradox where rural low-income families from states considered prosperous were persistently more food insecure than similar families from less prosperous states. An examination of quantitative and qualitative data found that families in the food insecure states were more likely to experience greater material hardship and incur greater housing costs than families in the food secure states. Families in the food insecure states, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…For example, in food insecure households, children may express feelings of hunger, but parents are unable to adequately respond because of insufficient supply of food in the home (Sano, Garasky, Greder, Cook, & Browder, ). Food‐insecure individuals may engage in acts to minimize appetite, such as smoking cigarettes, ignoring mealtimes, or drinking caffeinated beverages (Mammen, Bauer, & Richards, ). The USDA's screening tool for food insecurity also identifies lack of satiety as a key factor, by connecting food insecurity with eating less than desired or not eating enough to satisfy hunger (Bickel et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in food insecure households, children may express feelings of hunger, but parents are unable to adequately respond because of insufficient supply of food in the home (Sano, Garasky, Greder, Cook, & Browder, ). Food‐insecure individuals may engage in acts to minimize appetite, such as smoking cigarettes, ignoring mealtimes, or drinking caffeinated beverages (Mammen, Bauer, & Richards, ). The USDA's screening tool for food insecurity also identifies lack of satiety as a key factor, by connecting food insecurity with eating less than desired or not eating enough to satisfy hunger (Bickel et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the coping strategies is the reduction in the dietary intake manifested through either reduced number of meals or size of meals [4], [38], [52]–[54]. Poor dietary practices in food constrained situations emanate from the behavioral adaptations in response to food shortage [4], [55]. As reported by Norhasmah et al 2010[4], food related coping strategies follow sequential steps that progress into temporary alteration of the dietary intake patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The policies used by federal and state agencies to determine housing support need to be reconsidered. Research has shown that housing costs are the biggest budget item, and long‐term stable housing influences food security (Bartfield, Dunifon, Nord & Carlson, 2006; Mammen, Bauer, & Richards, 2009). Providing housing support for longer periods of time may assist young women to find stable jobs and/or complete their educations.…”
Section: Discussionmentioning
confidence: 99%